PENGARUH MARKET VALUE ADDED (MVA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR INDUSTRI LOGAM DI BURSA EFEK INDONESIA - Dede Suharna; Furniawan Furniawan; Eko Puryanto (Universitas La Tansa Mashiro, 2021)
A company value can have a positive impact on the company itself, its stakeholders, and its shareholders. This study aims to test and analyze the effect of Market Value Added and Debt to Equity Ratio on a company value that is proxied in the metal industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2017-2019. The method used in this research is quantitative methods. The population in this study were 13 metal industry sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. And using purposive sampling technique. The analysis technique used is multiple linear regression analysis using the SPSS v.20 program. The results of research on the product moment correlation analysis show that the relationship between Market Value added to firm value has a moderate correlation value, then the Debt to Equity Ratio to firm value has a very low correlation. The multiple correlation analysis test has a moderate relationship between the independent interval and the dependent variable. The results for the t test showed the effect of Market Value Added on firm value partially, while the debt to equity ratio variable partially had no effect on firm value. As for the f test, there is a significant influence between Market Value Added and Debt to Equity Ratio on firm value simultaneously. Based on the data analysis, it is concluded that the simultaneous Market Value Added and Debt to Equity Ratio have a significant effect on firm value. And partially only Market Value Added which has a significant effect while Debt to Equity has no effect on firm value.